Model Konseling Rekonsiliasi Di Rifka Annisa: Studi Kasus Pelaku Dan Korban Kekerasan Seksual - Sahentendi, Dianita; Tampake, Tony; Lauterboom, Mariska (Universitas Palangka Raya, 2025)
The high number of sexual violence against women is an important alarm for special attention from every element of society in preventing and handling the issue of sexual violence. So that sexual violence becomes one of the important issues that researchers will raise in this study. To break the chain of sexual violence, researchers believe that both perpetrators and victims must be involved in every existing process, for that reconciliation counseling is needed to bridge the process. This paper aims to describe and analyze how the reconciliation counseling model is carried out by Rifka Annisa for perpetrators and victims of sexual violence. The method used is qualitative research with a phenomenological approach, and interviews and documentation as methods in data collection. The results of this study found that reconciliation counseling was carried out for perpetrators and victims of violence including sexual violence who were married couples, this counseling was carried out based on the desire of both parties to repair their relationship in the hope that violence would not recur or based on reports received, in the process Rifka Annisa has the awareness that violence in any form including sexual violence can be stopped if the perpetrators and victims are both handled and committed to no longer experiencing sexual violence.